2009
DOI: 10.1007/s11424-009-9164-8
|View full text |Cite
|
Sign up to set email alerts
|

A single server retrial queue with general retrial times and two-phase service

Abstract: An M/G/1 retrial queue with a first-come-first-served (FCFS) orbit, general retrial time, two-phase service and server breakdown is investigated in this paper. Customers are allowed to balk and renege at particular times. Assume that the customers who find the server busy are queued in the orbit in accordance with an FCFS discipline. All customers demand the first "essential" service, whereas only some of them demand the second "optional" service, and the second service is multioptional. During the service, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In some queueing situations all arriving customers require the essential service, whereas a few of them may further demand the subsidiary service provided by the same server immediately after completion of the regular service. Several researchers have studied the concept of additional optional service with queues [11,19,20]. Jeganathan [9] investigated a continuous review perishable (s, S) inventory system with N optional services, in which some of the arriving customers asked for second optional service as soon as the completion of first essential service and the second service is multi-optional.…”
Section: Introductionmentioning
confidence: 99%
“…In some queueing situations all arriving customers require the essential service, whereas a few of them may further demand the subsidiary service provided by the same server immediately after completion of the regular service. Several researchers have studied the concept of additional optional service with queues [11,19,20]. Jeganathan [9] investigated a continuous review perishable (s, S) inventory system with N optional services, in which some of the arriving customers asked for second optional service as soon as the completion of first essential service and the second service is multi-optional.…”
Section: Introductionmentioning
confidence: 99%
“…Retrial queues with quasi-random input are of recent interest in modelling magnetic disk memory systems, telephony, cellular mobile networks, computer networks and localarea networks with non-persistent CSMA/CD protocols (see for example, Falin and Artalejo, 1998). Due to their wide applications in above areas, there has been a rapid growth in the literature on retrial queues with a quasi-random input, readers may refer to Do et al (2014b), Dragieve (2013Dragieve ( , 2014, Roszik et al (2007), Wang and Li (2009), Wang et al (2011), Zhang and Wang (2013) and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…They also provided some interesting applications of the model. Wang and Li (2009) studied a single server retrial queue with general retrial times and two-phase service. Choudhury and Kalita (2009) dealt with the steady behaviour of an M/G/1 retrial queue which the server provides two phases of heterogeneous service under Bernoulli vacation.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Gomez-Corral (1999) discussed extensively an M/G/1 retrial queue with FCFS discipline and general retrial times. In recent years, several retrial models have been analysed with general retrial times, details of which may be found in Atencia and Moreno (2005), Chang and Ke (2009), Krishnakumar et al (2002b), Moreno (2004) and Wang and Li (2009).…”
Section: Introductionmentioning
confidence: 99%